Growth performance, intestinal microflora, incidence of pododermatitis and leg weakness in broiler chickens reared on litter floor or in cages - Silahuddin, Muhammad Zulfahmi (2017)
The study was conducted to determine the effects of different rearing systems on growth performance, intestinal microflora, incidence of pododermatitis (FPD) and leg weakness in male broiler chickens under the hot and humid tropical environment. A total of 200 day-old male broiler chicks (Cobb 500) were equally allocated to either multilayer battery cages with wire floors (CRS) or floor pens (FRS) with wood shavings. Both cages and floor pens were in a naturally-ventilated house. The body weights on day 42 and feed intake from day 1 – 42 of CRS broilers were significantly lower than the FRS group. However, the CRS broilers had significantly better overall (day 1- 42) FCR than those of FRS. On day 42, the incidence of pododermatitis (FPD) was higher in FRS, while in CRS there was no incidence of FPD recorded. The FRS birds had significantly higher counts of cecal Escherichia coli and significantly lesser Salmonella spp than CRS at 42 days of age. However, rearing system had negligible effect on cecal populations of Campylobacter spp and Clostridium spp. The FRS birds showed a significantly longer duration of latency to lie than their CRS counterparts which suggested that the former had lower incidence of leg weakness. In conclusion, cage rearing system appeared to benefit performance, lower incidence of pododermatitis and intestinal E. coli population in broiler chickens. However, cage system may have adverse effect on leg strength and intestinal Salmonella spp population. Thus, a bigger floor space should be allowed for caged broilers to improve leg strength and biosecurity should be reinforced to reduce intestinal Salmonella population.